Stigmatisasi dan Diskriminasi Terhadap Odha di Maumere dalam Terang Teologi Pemerdekaan Mangunwijaya - Selai, Yohanes Pranata; Nahak, Servinus H. (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
This article aims to analyze the experiences of stigma and discrimination experienced by People Living with HIV-AIDS (PLWHA) in Maumere-Flores. The authors conducted qualitative research using in-depth interviews and participatory observation at the Flores Plus Support-Maumere Peer Support Group (KDS) from December 2022 to March 2023. Using the concept of Mangunwijaya’s theology of independence, this article analyzes the experiences of the suffering of PLHIV. According to Mangunwijaya, humans must be free from various forms of injustice that degrade their dignity. Two indicators for assessing the struggles of PLWHA are awareness of experiences of oppression and aspirations for self-determination. The results of this study indicate that situations of slavery as opposed to true freedom are still often experienced by PLHIV in Maumere. They are labeled as disgrace person, shunned by their families, or even thrown out of their homes. However, on the other hand, they are also aware of their suffering and try to find a way out of these various traumatic experiences.Abstrak Artikel ini bertujuan untuk menganalisis pengalaman stigma dan diskriminasi yang dialami Orang dengan HIV dan AIDS (ODHA) di Maumere-Flores. Untuk membahas masalah ini penulis melakukan penelitian kualitatif dengan wawancara mendalam dan observasi partisipatoris di Kelompok Dukungan Sebaya (KDS) Flores Plus Support-Maumere dari Desember 2022 s/d Maret 2023. Dengan menggunakan konsep Teologi Pemerdekaan Mangunwijaya artikel ini menganalisis pengalaman penderitaan para ODHA. Menurut Mangunwijaya, manusia harus merdeka dari aneka bentuk ketidakadilan yang merendahkan martabatnya. Dua indikator untuk menilai perjuangan pembebasan para ODHA yakni kesadaran akan pengalaman ketertindasan dan aspirasi untuk menentukan nasib sendiri. Hasil  penelitian ini menunjukkan bahwa situasi perbudakan sebagai lawan dari kemerdekaan sejati masih sering dialami para ODHA di Maumere. Mereka dicap sebagai pembawa aib, dijauhkan keluarga, atau bahkan diusir dari rumah. Namun, di sisi lain, mereka juga sadar akan situasi penderitaan mereka dan berusaha mencari jalan keluar dari berbagai pengalaman traumatis tersebut.